(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article analyzes the relationship of man to the world, historical importance, thinking, consciousness and views, the history of the development of spiritual and moral consciousness, views, different attitudes and approaches to the place of man in society.